Cognitive Decline Among the Middle-aged Living in the Coastal Area in Lombok Island - Suryani, Dini; Harahap, Herpan Syafii; Rivarti, Arina Windri; Nurhidayati; Zubaidi, Fitriannisa Faradina; Saputri, Legis Ocktaviana (Acta Neurologica Indonesia, 2025)
INTRODUCTION: Dementia is a leading cause of disability, dependency and poor quality of life. Its prevalence has increased consistently in recent years. Coastal communities who have limited access to health services have a higher risk of developing degenerative diseases including dementia. METHOD: A total of 154 middle-age peoples from four coastal area were recruited in this study. Participants were interviewed to obtain data on sociodemographic characteristics, lifestyle and medical history, then completed neuropsychological tests. Cognitive function was assesed by Mini-cog instruments. RESULT: The number of participants with cognitive decline was 87 people (56%) out of a total of 154 participants. 66% of all participants with cognitive decline were female. History of hypertension (67%), DM (16%), 40% with a BMI ≥22.5, 23% with a history of smoking, and 45% of participants with a low activity level. Multiple linear regression shows that Age and history of Hypertension is associated with cognitive decline (Sig.0.005 and 0.037). DM, BMI, smoking history and activity level is not associated significantly. CONCLUSION: More than half of middle age people on the coast of Lombok Island have cognitive decline. Age and history of hypertension are influencing factors.